2021
DOI: 10.1016/j.metop.2021.100081
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and Mediterranean diet in the context of obesity. Current knowledge, perspectives and potential therapeutic targets

Abstract: Mediterranean Diet has been recognized as one of the healthiest and sustainable dietary patterns worldwide, based on the food habits of people living in the Mediterranean region. It is focused on a plant-based cuisine combining local agricultural products and moderate intake of fish. As eating habits seem to exert a major impact on the composition of gut microbiota, numerous studies show that an adherence to the Mediterranean diet positively influences the microbiome ecosystem network. This has a profound effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…Several studies have reported that the gut microbiota production of SCFA can reduce several inflammatory and allergic diseases [47]. A higher consumption of fruits, vegetables, and legumes is linked to an increase in faecal SCFA levels as well as to higher concentration of microorganisms capable of degrading fibre [48]. Thus, the gut microbiota composition linked with higher MD adherence could be mediating the anti-inflammatory profile observed in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the gut microbiota production of SCFA can reduce several inflammatory and allergic diseases [47]. A higher consumption of fruits, vegetables, and legumes is linked to an increase in faecal SCFA levels as well as to higher concentration of microorganisms capable of degrading fibre [48]. Thus, the gut microbiota composition linked with higher MD adherence could be mediating the anti-inflammatory profile observed in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of dietary fiber are possibly through higher SCFAs production, as SCFAs are synthesized through fermentation of indigestible fibers by the commensal GM [ 134 ]. As the MD has substantial larger amounts of fibers, studies have found higher amounts of SCFA production with this diet, and furthermore the diet has shown to decrease Firmicutes while increasing Bacteroidetes phyla, which is relevant because Bacteroidetes is associated with increased SCFAs production [ 195 ]. Whether GM composition is merely a biomarker of the diet consumed is becoming less likely, as the diet rather appears to play an active role in altering GM composition and mediate its cardiometabolic-associated diseases.…”
Section: Gut Microbiota Metabolites In Dietary Weight Loss and Pharmacologic Interventionsmentioning
confidence: 99%
“…A plethora of meta-analyses have shown that adherence to the MedD reduces CV risk factors including hard endpoints [ 85 , 86 ]. Moreover, research also suggests that the MedD can be an effective remedy for precursors of CVD, including hypertension or obesity [ 87 , 88 , 89 ]. Nevertheless, great heterogeneity is observed with respect to the trials implementing MedD interventions, their design, fragility index, and intervention characteristics, as well as regarding what is considered as a MedD by definition [ 54 ].…”
Section: Discussionmentioning
confidence: 99%